Subjects of industrial property right in different kinds of economic activity within the forest sector of Ukrainian economy - Onufryk , Igor (Forestry, Forest, Paper and Woodworking Industry, 2007)
The state of inventive activity is analyzed through reviewing the subjects of industrial property right in different kinds of economic activity within the forest sector of Ukrainian economy. A low level of innovative activity in this economic sector is stated, which significantly diminishes its innovative attractiveness. The ways out of this innovative activity’s decay in the forest economic sector are suggested.